CHANGES IN UTERINE CAPABILITY DUE TO INCREASED LITTER SIZE AT 7 WEEKS OF PREGNANCY IN KACANG GOAT - Arif, Ridi; Satrija, Fadjar; Winarto, Adi; Boediono, Arief; Manalu, Wasmen (Universitas Syiah Kuala, 2018)
The purpose of this research was to study the changes in uterine support capability power due to increase of litter size in Kacang goat. In this study, 9 pregnant female Kacang goats were divided into 4 different groups based on litter size, namely 1, 2, 3, and 4. At 7 weeks of pregnancy, the experimental Kacang goats were sacrificed to observe the macro and micro parameters of the uterus. The results showed that the litter size had a quadratic relationship with micro parameters of uterus but it had a linear relationship with macro parameters of the uterus. The variables of uterine glands area, glands lumen area, and cytoplasmic area reached maximum condition at the litter size of 2.5. Litter size had a linear relationship with the volume, weight, and dimension of the uterus. It can be concluded that the optimal number of litter size in Kacang goat was two offsprings which was proven by the optimal function of the uterus to support fetal development.